The concept and classification of labor disputes - Issayeva А.Zh.; Aitimov, B.Zh. (Bulletin of the Karaganda University “Law Series”, 2020)
Various approaches to define the types of labor disputes are analyzed in this article, general criteria for the classification of both individual and collective labor disputes are offered. The purpose of the publication is to identify the practical orientation of these theoretical provisions. A study of the dependence of the definition of the method and procedure for resolving a labor dispute on its subject and subject composition is carried out. Various approaches of the legislator to the solution of this issue, both at the present time and in the historical aspect, are demonstrated. It is pointed out that it is necessary to admit the resolution of collective labor disputes on law in court; for individual labor disputes of interest, provide for a conciliation procedure. Moreover, attention is paid to the theoretical aspect of the labor dispute, including the concept and classification of labor disputes, as well as certain types of disagreements between the employee and the employer on the establishment and application of the current labor and other social legislation, which is not allowed in direct negotiations with the employer and was the subject of office work in specially authorized bodies.